(untitled) (Journal of Economic Research & Business Administration, 2023)
The primary aim of this research is to assess how sustainability corporate governance influences the disclosure of environmental practices by manufacturing companies listed in Nigeria. The research methodology employed in this investigation is ex-post facto, also referred to as a retrospective or causal-comparative design. The study’s sample comprises ten selected listed manufacturing companies, chosen through purposive sampling techniques. Data for the study was gathered from sustainability reports and annual reports of these manufacturing firms listed on the Nigerian Stock Exchange (NSE). To investigate the relationships specified in the model, Ordinary Least Squares (OLS) regression analysis was applied. The coefficients for CSO (Chief Sustainability Officer) and EC (Environmental Committee) are 0.152 and 0.119, respectively. Their corresponding t-test values of 6.156 and 3.111 demonstrate statistical significance at the 5% level (p < 0.05). In contrast, the coefficient for SRC (Sustainability Reporting Committee) is 0.052, with a t-test value of 1.980, and a p-value exceeding 0.05 (p > 0.05). The research findings highlight significant connections between sustainability corporate governance practices and the disclosure of corporate environmental activities. Notably, Chief Sustainability Officers and Environmental Committees play influential roles in promoting more comprehensive and transparent environmental reporting practices among the listed manufacturing companies. Top of Form Key words: Sustainability Corporate Governance (SCG), Corporate Environmental Disclosure (CED), Environmental Committee, Corporate Governance, Sustainability, Environmental Performance, Environmental Impacts